2007
DOI: 10.1542/peds.2007-0360
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors Associated With Fever in Children With Autism Spectrum Disorders

Abstract: We documented behavior change among children with autism spectrum disorders during fever. The data suggest that these changes might not be solely the byproduct of general effects of sickness on behavior; however, more research is needed to prove conclusively fever-specific effects and elucidate their underlying biological mechanisms (possibly involving immunologic and neurobiological pathways, intracellular signaling, and synaptic plasticity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
100
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 18 publications
4
100
2
2
Order By: Relevance
“…Notably, the degree of improvement (mostly in stereotypic behavior and inappropriate speech) was unrelated to the severity of fever or of autism (21). This study explicitly suggested that elucidation of the fever response might provide insight into the mechanisms of ASD and point to new therapeutic approaches (21,22).…”
Section: Significancementioning
confidence: 69%
See 2 more Smart Citations
“…Notably, the degree of improvement (mostly in stereotypic behavior and inappropriate speech) was unrelated to the severity of fever or of autism (21). This study explicitly suggested that elucidation of the fever response might provide insight into the mechanisms of ASD and point to new therapeutic approaches (21,22).…”
Section: Significancementioning
confidence: 69%
“…Fourth, widespread anecdotal reports have suggested that fever can dramatically but temporarily ameliorate the disturbed behavior of many autistic patients (21). Notably, the degree of improvement (mostly in stereotypic behavior and inappropriate speech) was unrelated to the severity of fever or of autism (21).…”
Section: Significancementioning
confidence: 96%
See 1 more Smart Citation
“…Following is Dr. Kinsbourne's response. Curran et al (2007) confirmed that children with autism behave less aberrantly when they are febrile due to infections, a phenomenon that might offer insight into the cause and treatment of autistic symptoms. Good (2011) attributes the improvement to an increase in cerebral blood flow.…”
mentioning
confidence: 69%
“…Evidence is lacking that fever increases the perfusion of these regions, or that they would function better if it did. Indeed, Curran et al (2007) found no relationship between degree of fever and degree of improvement.…”
mentioning
confidence: 94%